ANALISIS KINERJA PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH PEMERINTAH KOTA MALANG - Samuel Eddy Gunawan (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
The Budget Realization Report (LRA) is an accountability report for the use of Regional Revenue and Expenditure Budget (APBD) which contains the budget targets and budget realization. This research was conducted on three parts of APBD namely income, expenditure, and financing. This research activity is carried out at City Government (Pemkot) Malang, East Java Province. From the result of variance analysis, the performance of revenue management of Malang City Government can be said good because found favorable variance condition in most of income period of year 2007 until 2011. PAD growth and local tax is positive and have tendency to increase and local tax and levy is biggest contributor in PAD . However, in terms of efficiency of APBD implementation is classified as less efficient. Growth is positive and has a tendency to always go up. In addition to personnel expenditure, the allocation of funds is mostly for operating expenditure. The efficiency of spending, there is no waste of budget. In addition, Malang City Government has also done the control and budget planning. In the financing section, the analysis shows that the budget planning of Malang City Government from year to year is still less precise.